New Perspectives on Microsoft Office PowerPoint 2003, Comprehensive - S.Scott Zimmerman (Cengage Learning, Inc, 2006)
Part of the New Perspectives series, this text offers a case-based, problem-solving approach and innovative technology for meaningful learning of Microsoft PowerPoint 2003